Intermolecular Coulombic decay in liquid water competes with proton transfer and non-adiabatic relaxation - Pengju Zhang; Joel Trester; Jakub Dubský; Přemysl Kolorenč; Petr Slavíček; Hans Jakob Wörner (Nature Communications)
Abstract Despite decades of research, our understanding of radiation damage in aqueous systems remains limited. The recent discovery of Intermolecular Coulombic Decay (ICD) following inner-valence ionization of liquid water raises interesting questions about its efficiency as a major source of low-energy electrons responsible for radiation damage. To investigate, we performed electron-electron coincidence measurements on liquid H2O and D2O using a monochromatized high-harmonic-generation light source, detecting ICD electrons in coincidence with photoelectrons from the 2a1 shell. We find that the ICD efficiency γ is below unity in both liquids and that γ(H2O)/γ(D2O) = 0.86 ± 0.03. Ab initio calculations reveal that ICD competes with proton transfer and non-adiabatic relaxation, which can close the ICD channel. A multi-scale stochastic model incorporating solvent effects reproduces these efficiencies. Our combined experimental and theoretical results suggest that the higher ICD efficiency in D2O arises from slower proton transfer and non-adiabatic transitions, highlighting the crucial role of nuclear motion in liquid-phase ICD and advancing the understanding of radiation damage.